2012
DOI: 10.1080/10852352.2012.633064
|View full text |Cite
|
Sign up to set email alerts
|

The Mediational Role of Values in Linking Personality Traits to Civic Engagement in Italian Youth

Abstract: In recent decades, given new forms of political participation, the involvement of young people in the civic domain begins to be a focus of many studies. The present study examined the role of personality traits and personal values in the prediction of civic engagement (CE) in Italian youth ranging in age from 19 to 29 years old involved in an ongoing longitudinal study. The multidimensionality of a scale tapping CE has been demonstrated with the examination of confirmatory factor analysis. Structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
(43 reference statements)
2
12
0
Order By: Relevance
“…Civic involvement may take many forms such as active membership in various nonprofit organizations, volunteering, participation in community programs, and other actions aiming to promote the welfare of people and the community (e.g., Omoto, Snyder, & Hackett, 2010). Past research has found that civic involvement was positively associated with self‐transcendence values (e.g., Luengo Kanacri, Rosa, & Di Giunta, 2012; Radkiewicz, De Zavala, & Skarżyńska, 2008). Self‐transcendence expresses the motivation for concern and care for others (Schwartz, 1992).…”
Section: The Current Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Civic involvement may take many forms such as active membership in various nonprofit organizations, volunteering, participation in community programs, and other actions aiming to promote the welfare of people and the community (e.g., Omoto, Snyder, & Hackett, 2010). Past research has found that civic involvement was positively associated with self‐transcendence values (e.g., Luengo Kanacri, Rosa, & Di Giunta, 2012; Radkiewicz, De Zavala, & Skarżyńska, 2008). Self‐transcendence expresses the motivation for concern and care for others (Schwartz, 1992).…”
Section: The Current Researchmentioning
confidence: 99%
“…It is, therefore, consistent with actions aimed at promoting the quality of life in a community and protecting the interests of social groups. Accordingly, research has found that endorsing self‐transcendence values was positively associated with being members in various associations (e.g., Luengo Kanacri et al, 2012) and contributing to prosocial organizations (e.g., Arieli et al, 2014).…”
Section: The Current Researchmentioning
confidence: 99%
“…Zaff, Moore, Papillo, and Williams (2003) suggested that youths' attitudes and value systems contribute to the consistency of civic engagement over time. Young adults' values, such as benevolence and universalism, would be expected to have a strong relation to prosocial behaviors (e.g., Caprara, Alessandri, & Eisenberg, 2012) and civic engagement (Luengo Kanacri, Rosa, & Di Giunta, 2012). Whereas benevolence is related to concern for the wellbeing of people in close relationships (family, school, neighborhood), universalism is related to behaviors associated with helping people and society as a whole (Schwartz, 2006).…”
Section: Prosocial Behavior and Civic Outcomesmentioning
confidence: 99%
“…Chung and Probert (2011) highlighted the importance of individual outcome expectations. Kanacri, Rosa, and Di Giunta (2012) indicated the importance of psychological personality measures while Robles-Fernandez (2011) pointed to the importance of students' beliefs. Yet, there is a lack of studies that seek to identify values as an underlying mechanism that might account for civic learning and also provide the basis for civic action.…”
mentioning
confidence: 98%